Economic Policies and Programmes in India Some Observations - Planning Commission (Planning Commission, 1951)
India took to planning in 1951 with the primary objective of initiating a process of development which would raise living standards and open out to the people new opportunities for a richer and more varied life. Since then, three Five Year Plans, covering the period 1951-66, have been nearly completed.
Department of Economic and Market Research